(untitled) (Journal of history, 2020)
The article presents some results of integrated archaeological research on the medieval settlement of Dzhankent in 2019. Modern archaeological research the settlement Dzhankent started in the distant 1946, when the monument was visited by the head of the Khorezm Archaeological and Ethnographic expedition S.P. Tolstov with flight intelligence group, which brought together lift the material and produced a visual map of the site. Stationary archaeological research began only in 2005 as part of a tripartite agreement between the Institute of Ethnology and Anthropology. N.N. Maclay, Russian Academy of Sciences, the Institute of Archaeology. A.H. Margulan MES RK and Kyzylorda state University. Korkyt Ata MES RK. For 15 years of field research, a huge amount of material has been accumulated on the material culture of the tribes that inhabited the settlement of Dzhankent. However, until now, the defensive structures and the structure of the main entrance gate of the monument have not been well studied. To fill the above gap in 2018 was laid excavation number 7 on the Eastern gate of the settlement. During two field seasons, 200 m2 were excavated at excavation 7 and several construction horizons were revealed. Previously, it can be argued that the main entrance gate of Dzhankent was built by analogy with the nearby cities of southern Khorezm.